Efficiency of local budget expenditures: control mechanism in Scotland and lessons for Ukraine - MALYNIAK, Bohdan; PIDLISNY, Ivan (Scientific journal «World of Finance», 2019)
Introduction. The system, wich is designed to ensure the rational use of budget funds, functions in Ukraine imperfectly. It is important to scan the experience of foreign countries and introduce the best experience in domestic practice. Purpose is to formulate the scientific approaches to integrated assessment of the efficiency of local budget expenditures, considering foreign experience. Results. The mechanism for ensuring the efficient use of budgetary funds in Scotland is built in the modern period of history, considering current challenges, opportunities for implementation and the results of relevant scientific research. Implementation of measures to increase the efficiency of budget expenditures took place as a reaction to a high level of distrust of the government and its activities. The main measures aimed at controlling the effectiveness of budget expenditures are based on four basic provisions: the validity of budget revenues and expenditures, their balance; priority of budget expenditures; the value and quality of public services; organization of the budget process, namely the integration of planning of management and financial activities. The main findings of the study of the experience of financial control in Scotland are as follows: the complexity of financial control over the efficiency of budget expenditures, the integration into the system of tools for reforming the budget process, developed methods for evaluating the efficiency of local budget expenditures are universal for different entities of control. Based on the experience of ensuring the efficiency of budgetary expenditures in Scotland, it is substantiated that the efficiency of budget expenditures is not appropriate to be determined by a specific indicator, but it is appropriate to comprehensively assess the compliance of expenditures with a number of criteria. The most important of them should be four criteria: observance of democratic procedures for planning and implementation of the local budget; assessment of compliance of budget expenditures with public priorities; analysis of budget programs implementation and achievement of planned targets; exploration of the value of services. The research-based criteria for assessing the effectiveness of local budgets are important not only for the development of the concept of building a control system, but also have an applied value. The methodological approaches formulated in research were applied in the research both of the local budget and of a separate line of expenditures. Conclusions. The experience of the organization of financial control of the efficiency of budgetary expenditures in Scotland indicates a number of its positive qualities, which make it possible to realize the main purpose of government policy - to increase the level of public confidence in the government. Methodological approaches to the organization of monitoring the effectiveness, are formulated on the basis of Scottish experience. The developed approaches can be applied not only in scientific researches, but also they are suitable for application. Ulterior scientific research may focus on formalizing the methodology for analyzing the efficiency of local budget expenditures. This will enable, in particular, to substantially expand the applied component of methodological approaches and facilitate their application in practice, which is important given the continued growing topicality of the effective management of local budgets in terms of expanding their resources and critical assessment of the society’s effectiveness of their use.